Phenolic profile, safety assessment, and anti-inflammatory activity of Salvia verbenaca L. (23rd May 2021) - Righi, Nadjat; Boumerfeg, Sabah; Deghima, Amirouche; Fernandes, Pedro A.R.; Coelho, Elisabete; Baali, Faiza; Cardoso, Susana M.; Coimbra, Manuel A.; Baghiani, Abderrahmane
Abstract: Ethnopharmacological relevance: Salvia species are known to have anti-inflammatory properties, and are traditionally used for healing purposes. Salvia verbenaca is an Algerian plant used for healing wounds and ulcers. Aim of the study: This work aims to assess the acute and subacute safety of S. verbenaca and its possible anti-inflammatory activity as a mechanism contributing to its traditional applications. Materials and methods: Lethal toxicity of S. verbenaca hydromethanolic extract was evaluated against Artemia salina larvae, while acute and subacute toxicity were orally tested on mice. The anti-inflammatory activity was screened ex vivo using membrane stabilization and in vivo using xylene induced ear edema as an acute inflammation model. The antiradical, reducing power and iron chelating activities of S. verbenaca were also investigated in vitro, and phenolic compounds were determined using UHPLC-DAD-ESI-MS n . Results: Salvia verbenaca extract contained high amounts of phenolic compounds (206 μg GAE/mg extract). The in vitro antioxidant activity showed promising radical scavenging ability, iron chelating (IC50 : 189 μg/mL), reducing power and strong anti-lipid-peroxidation effect (IC50 : 111 μg/mL). The extract had potential cytotoxic effect against Artemia salina larvae (LC50 : 30 μg/mL), but did not exhibit any acute/subacute toxicity effect on mice. Salvia verbenaca inhibited hypotonic and heat induced hemolysis and also reduced 50% of xylene induced ear edema at 600 mg/kg bw. Rosmarinic acid and caffeoylmalic acid were identified as the major compounds. Conclusion: Salvia verbenaca hydromethanolic extract was found to be safe at acute and subacute levels. Its in vitro/in vivo antioxidant activity, membrane stabilizing properties and anti-inflammatory activity may be an important aspect of its wound healing and anti-ulcer traditional use. Graphical abstract: Image 1 Highlights: Salvia verbenaca hydromethanolic extract did not exhibit oral acute or subacute toxicity. In addition, it showed cell membrane stabilization and anti-inflammatory properties. Hydromethanolic extract from S. verbenaca presented antioxidant activity. Major compounds identified were rosmarinic, caffeoylmalic, and yunanneic acids.